Integrating Islamic Boarding School Ecosystems and Islamic Religious Education in Shaping the Religious Character of Generation Z: A Systematic Literature Review - Hanafi; Saimun (Al-Qalam Institue, 2026)
The rapid development of Generation Z in the digital era poses significant challenges to the internalisation of religious values, thereby necessitating a holistic and adaptive model of Islamic education. This study aims to examine the role and contribution of the religious ecosystem of Islamic boarding schools (pesantren) and Islamic Religious Education (PAI) in shaping the religious character of Generation Z. Employing a Systematic Literature Review (SLR) approach, this study analyses 40 peer-reviewed articles published between 2017 and 2025 and retrieved from Google Scholar, Scopus, Web of Science, ERIC, and DOAJ. Data were analysed through a structured process of article selection, thematic categorisation, and comparative synthesis. The findings reveal that the religious ecosystem of Islamic boarding schools, when integrated with PAI, plays a strategic role in internalising values of faith, piety, and moral conduct through role modelling, religious habituation, and the cultivation of a sustainable religious culture. These findings highlight the capacity of pesantren to foster holistic religious character formation that addresses both spiritual and psychological dimensions of Generation Z. The study implies that Islamic boarding schools remain a relevant and effective model of religious character education capable of responding to the moral and psychological challenges faced by contemporary youth in the digital era.